Relationship between Maternal Attitudes, Subjective Norm, and Perceived Behavior Control with Intention of Basic Immunization Perceived among Babies at the Pademawu Public Health Center, Pamekasan Regency, Indonesia - Handinis Sonya Ringtiyas; Hilmah Noviandry; Lailatul Hafidah; Adi Sutrisni (Alta Dharma Publisher, 2020)
One of the effective efforts to reduce child mortality is by giving immunization. The study aimed to examine the relationship between attitudes, subjective norms, and perceived behavior control on the intention of basic immunization perceived among babies. A cross-sectional study was applied in this study. One hundred thirty-nine samples were carried out by using simple random sampling. The data analyzed using Logistic Regression with a significance level (? = 0.05). The results showed that attitude (p = 0.000), norms (p = 0.025)and perceived behaviors controls (p = 0.000) have positive correlation with the basic immunization for babies. The mother's intention in giving basic immunization to the baby was influenced by attitudes, subjective norms, and perceived behavior control for giving basic immunization to the babies. Attitudes, subjective norms, and perceived behavior control will form the mother's intention to give basic immunization to the baby. Counseling and espionage will be needed for mothers and families to give basic immunizations to the babies because giving it prevents the occurrence of diseases that can be caused by immunization